2017
DOI: 10.5565/rev/ensciencias.2338
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de las competencias ambientales del profesorado de primaria en formación inicial: estudio de caso

Abstract: En este artículo se evalúan las competencias ambientales (CA) del profesorado en formación inicial al comienzo y en la finalización del Grado de Maestro/a en Educación Primaria (GMEP) en una universidad española. Se ha desarrollado y validado un cuestionario con el fin de evaluar seis CA en relación con los conocimientos, las actitudes y los comportamientos ambientales de los y las estudiantes de la muestra (n = 341). Los resultados del estudio revelan que el profesorado en formación inicial carece de las CA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
21

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 13 publications
2
19
0
21
Order By: Relevance
“…After the experience, the students interviewed seemed to understand that their consumer habits affect society and the environment, but they are not prepared to change their ways, showing again the "breach" that can exist between cognition and action, as noted by various authors [59,60]. Studies, such as that by Álvarez, Sureda, and Coma (2018) [17] carried out in a similar Spanish context, also point to the poor commitment to action in solving socio-environmental problems by future teachers who have a high level of environmental awareness.…”
Section: Speaking About Our Socioeconomic Model and Our Responsibilitmentioning
confidence: 98%
See 1 more Smart Citation
“…After the experience, the students interviewed seemed to understand that their consumer habits affect society and the environment, but they are not prepared to change their ways, showing again the "breach" that can exist between cognition and action, as noted by various authors [59,60]. Studies, such as that by Álvarez, Sureda, and Coma (2018) [17] carried out in a similar Spanish context, also point to the poor commitment to action in solving socio-environmental problems by future teachers who have a high level of environmental awareness.…”
Section: Speaking About Our Socioeconomic Model and Our Responsibilitmentioning
confidence: 98%
“…Although there is concern for the environment among teacher trainers, many of these initiatives base their curriculum focus on increasing teachers' awareness of environmental issues and environmental content knowledge, but few address key issues associated with the need to change worldviews [13]. Thus, study has shown that the basic training of teachers has important shortcomings regarding Environmental Education, sustainability, and climate change [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Higher Education (HE), it can be said that it is a source of learning about more pro-environmental private and professional lifestyles for students. For that reason, this level of education can act as a driving force in the acquisition of knowledge, attitudes, habits, and ultimately, competencies that help develop sustainability in our daily lives as a tool to improve and preserve the environment [10,18,45,46,[52][53][54]. Planning and implementation, empathy, compassion, and solidarity, among others, are highlighted as key competences favouring SRSD [55].…”
Section: Introductionmentioning
confidence: 99%
“…This being said, reality shows that there is still a long way to go and that ESD could be implemented more extensively in university studies [29,45,53,56,[62][63][64]66]. This is highly relevant in the case of teachers who are training to be professionals who will practice in any society where education is compulsory.…”
Section: Introductionmentioning
confidence: 99%
“…Universities have tried to implement environmental education as a cross-disciplinary subject in the official syllabus; it was the establishment of the Network for the Curriculum’s Environmental of Higher Education in Spain (ACES Network) [28]. Despite this fact, insufficient levels of environmental literacy are seen in future teachers [30]. Indeed, it is necessary to give trainee teachers in primary education environmental education, so that they can later share their knowledge with future generations [12,31].…”
Section: Introductionmentioning
confidence: 99%